A Further Result about "On the Channel Capacity of Multiantenna Systems with Nakagami Fading". (19th April 2007) - Nadarajah Nadarajah, Saralees Saralees; Kotz Kotz, Samuel Samuel
Abstract : Explicit expressions are derived for the channel capacity of multiantenna systems with the Nakagami fading channel.